Reflecting on the Role of BPN in Protecting Land Ownership Rights Holders Above HPL in Batam City - Wahyudi, Andre (Jurnal Konstatering, 2024)
The development of the HPL management policy in Batam City shows thatThere is a dualism in the concept of land ownership rights over HPL that occurs in Batam City, this can be seen from the existence of the Batam Industrial Management Agency mechanism which can grant Ownership Rights to parties who buy land over HPL land in Batam City, as a result of this, the owner of the Ownership Rights for land over HPL does not fully own the land that he has purchased, because the HPL is still valid on his land. BPN, which is the party that should take action to prevent buyers of land above HPL from being harmed, still seems passive. The type of legal research used is non-doctrinal. In this non-doctrinal legal research, law is conceptualized sociologically as an empirical phenomenon that can be observed in life. Based on the study conducted, it can be found that the fact that he National Land Agency has not been able to provide complete information and counseling to prospective land buyers or the community regarding the lack of legal certainty in the status of land ownership above HPL land, this has resulted in most people buying land above HPL owned by BP, this situation clearly results in legal uncertainty for the protection of land ownership rights for buyers considering that there are no clear regulations related to land ownership rights above BP HPL in Batam City. The solution that can be done is that there needs to be an affirmation regarding the absence of changes in HPL to land ownership rights above BP's HPL, there needs to be regulation of restrictions on BP's authority in terms of issuing decisions on the transfer of HPL to land ownership rights on HPL, and there needs to be a re-registration of land that before the existence of BP's HPL had been previously occupied and used by the community.Keywords: Land; Ownership; Protecting; Role.